(untitled) (Research, Society and Development, 2025)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental condition characterized by inattention, disorganization and hyperactivity-impulsivity, with a prevalence ranging from 5% to 7% in children and 2% to 6% in adults. Frequently associated with clinical and behavioral comorbidities, ADHD is linked to dysfunctions in the prefrontal cortex—responsible for attention control, inhibition, and decision-making—affecting self-regulation and increasing susceptibility to poor eating behaviors and nutritional deficiencies. This study aimed to analyze the impact of ADHD diagnosis on eating behavior across different life stages, with an emphasis on childhood and adolescence. A qualitative literature review was conducted using studies published between 2014 and 2025 from SCIELO, PUBMED, BIREME, PsycINFO, and SCOPUS databases. Findings indicate that individuals with ADHD are more likely to adopt inadequate dietary patterns, have insufficient micronutrient intake, and show a higher risk for eating disorders. Impulsivity and self-regulation difficulties were identified as key factors contributing to dysfunctional eating choices, with long-term consequences on nutritional status and increased risk of comorbidities in adulthood, especially in the absence of early interventions. ADHD management should involve a multidisciplinary approach, including nutritional, behavioral, and psychotherapeutic strategies. Within this scope, adherence to healthy dietary patterns, such as the Mediterranean diet, along with omega-3 fatty acid and micronutrient supplementation, appears promising in symptom modulation. Nutritional intervention thus emerges as a crucial component in improving health outcomes and quality of life for individuals with ADHD throughout the life course.